Monitoring Intensity, Institutional Shareholders, and Earnings Manipulation Engendered Accounting Scandal: The South African Perspective - Obagbuwa, Oloyede; Kwenda, Farai; Baldavoo, Kiran (International Journal of Economics and Financial Issues, 2024)
This study determines the extent to which loosening institutional shareholder monitoring intensity induces earnings management, thereby leading to accounting scandals. When there is intense monitoring of the corporate executives, their opportunistic tendencies are prevented, and corporate decisions align with the value-creation target. The study postulates that institutional shareholders’ relaxed monitoring role positively and significantly impacts earnings management. The more robust Two-Step System GMM was used to analyse the collected data of companies listed on the Johannesburg Stock Exchange (JSE) for 15 years from 2004 to 2019. The finding revealed that slack institutional shareholders’ control affects earnings management positively.